The Determination of Relevant Market on Islamic Financial Services Sector: Perspective of Indonesian Business Competition Law - Nasir, Rifqi Ridlwan; Kusnadi, Egi Hadi; Hidayah, Aziza Mutifani (Az-Zarqa': Jurnal Hukum Bisnis Islam, 2023)
Abstract: After promulgation of Act Number 4 of 2023 concerning the Development and Strengthening of Financial Sector, sharia financing service businesses consisting of Sharia Banking, Sharia Public Economic Banks and Sharia Microfinance Institutions (LKMS) have financing products that tend to be the same. This is related to the definition of the relevant market in Act Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. This study aims to analyze the relevant market and to find potential of anti-competitive behavior in the financial services business. It is a normative juridical research using qualitative analysis. The method is summarized by examining regulations and doctrines related to Indonesian Business Competition Law. The results of this study explain that Sharia Banking, Sharia Public Economic Banks, and LKMS have same relevant market because the only difference is the financing scale. The Sharia Banking as dominant sector can influence the climate of business competition. Based on CR4 theory, the market concentration ratio in the Islamic financial services sector is a market that leads to loose oligopoly. There needs to be a limitation on the scale of financing regarding the maximum value of financing in Sharia Banking area and how much is in the area of LKMS to reduce the potential for abuse of dominance. But, rule of reason approach is still needed to find out the occurrence of violations caused by corporate action. The rule of reason approach used to assess corporate actions is in accordance with the maslahah mursalah concept. Abstrak: Pasca diundangkannya Undang-Undang Nomor 4 Tahun 2023 tentang Pengembangan dan Penguatan Sektor Keuangan, pelaku usaha jasa pembiayaan syariah yang terdiri dari Perbankan Syariah, Bank Perekonomian Rakyat Syariah, dan LKMS mempunyai produk pembiayaan yang cenderung sama. Mereka masih merupakan satu kesatuan dari iklim persaingan atau pasar yang bersangkutan. Hal ini terkait dengan pengertian pasar bersangkutan dalam Undang-Undang Nomor 5 Tahun 1999 tentang Larangan Praktek Monopoli dan Persaingan Usaha Tidak Sehat. Penelitian ini bertujuan untuk menganalisis pasar bersangkutan dan mengetahui potensi perilaku anti persaingan pada bisnis jasa keuangan. Penelitian ini merupakan penelitian yuridis normatif dengan menggunakan analisis kualitatif. Metode tersebut dirangkum dengan mengkaji peraturan dan doktrin terkait Hukum Persaingan Usaha Indonesia. Hasil penelitian ini menjelaskan bahwa Perbankan Syariah, Bank Perekonomian Rakyat Syariah, dan LKMS mempunyai pasar bersangkutan yang sama karena yang membedakan hanyalah skala pembiayaannya. Perbankan Syariah sebagai sektor dominan dapat mempengaruhi iklim persaingan usaha di sektor jasa keuangan syariah. Berdasarkan teori CR4, rasio konsentrasi pasar pada sektor jasa keuangan syariah adalah pasar yang mengarah pada oligopoli longgar. Perlu adanya pembatasan skala pembiayaan terkait nilai maksimal pembiayaan yang menjadi wilayah Bank Syariah dan berapa yang menjadi wilayahnya LKMS untuk mengurangi potensi penyalahgunaan posisi dominan. Namun demikian, pendekatan rule of reason tetap diperlukan untuk mengetahui terjadinya pelanggaran yang diakibatkan oleh suatu aksi korporasi. Adapun pendekatan rule of reason yang digunakan untuk menilai aksi korporasi telah sesuai dengan konsep maslahah mursalah dalam Hukum Islam.